Pengembangan Modul Elektronik Berbasis Android Menggunakan Website 2 APK dengan Nilai-nilai Islam pada Materi Virus Peserta Didik SMA - Aprilia, Anggi; Sujarwanta, Agus; Widowati, Hening (Biotik, 2025)
Abstract: Innovations in education, including electronic teaching materials, enhance students' motivation and understanding, supported by technological advancements. However, the integration of technology in learning remains suboptimal, as observed in Biology education. The topic of viruses is considered difficult due to its abstract nature and complex scientific terminology, while instruction still relies heavily on textbooks with minimal use of technology. This study aims to develop an Android-based e-module on viruses, integrating Islamic values to facilitate students' understanding. The development follows the ADDIE model and is evaluated by experts before being tested with teachers and students. Validation results indicate a very high feasibility level (98% from subject matter experts, 99% from media experts, and 92% from Islamic values experts). The trial results show high approval ratings from teachers (93.7%) and students (90.1%), demonstrating that the e-module is highly effective in supporting engaging, flexible, and meaningful learning, applicable for both in-person and online education. Keyword: Electronic module 1; Android 2; virus 3; Islamic Values 4.